THE RELATIONSHIP BETWEEN PREMENSTRUAL SYNDROME, PSYCHOEMOTIONAL STATE, AND DEPRESSIVE SYMPTOMS IN ADOLESCENT GIRLS - MADRAXIMOVA DINORA ODILBEK QIZI; ISMAILOVA DILDORA O‘KTAMOVNA (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
l syndrome (PMS) is one of the most common cyclical disorders observed among adolescent girls and is characterized by a combination of physical, emotional, behavioral, and cognitive symptoms appearing during the luteal phase of the menstrual cycle and disappearing shortly after menstruation begins. During adolescence, when hormonal balance and emotional regulation are still developing, PMS may negatively influence psychological well-being, school performance, social interaction, and quality of life. This study aimed to investigate the relationship between PMS and psychoemotional disturbances, with particular attention to depressive symptoms among adolescent girls. A cross-sectional analytical study was conducted among girls aged 13–19 years using validated clinical questionnaires for PMS severity, emotional state, anxiety, stress, and depression. The results demonstrated that adolescents with moderate and severe PMS showed significantly higher levels of irritability, anxiety, emotional instability, sleep disturbances, and depressive symptoms compared with participants without PMS. The severity of PMS was positively associated with the intensity of depressive manifestations. These findings emphasize that PMS in adolescence should be considered not only a gynecological condition but also an important psychosocial and mental health issue requiring early identification and multidisciplinary management.